Osteocalcin and cross‑linked C‑terminal telopeptide of type I collagen in gingival crevicular fluid during piezocision accelerated orthodontic tooth movement: A randomized split‑mouth study - YILDIRIM, HATİCE SELİN; KURU, LEYLA (My University, 2023)
Background: Piezocision, a minimally invasive surgical procedure, has been used to accelerate tooth movement. Aim: The aim of this randomized split‑mouth study was to evaluate gingival crevicular fluid (GCF) osteocalcin (OC) and type I collagen cross‑linked C‑terminal telopeptide (ICTP) levels during canine distalization with and without piezocision acceleration. Material and Methods: Fifteen systemically healthy subjects (M:F 7:8, 16.27 ± 1.14 years) requiring extraction of maxillary first premolars before retraction of canines were included in the study. Piezocisions were randomly carried out on one of the maxillary canines while bilateral canines served as controls. Canine distalization was conducted using closed‑coil springs applying a force of 150 g/side by using miniscrews as anchorage. GCF sampling was performed from maxillary canine mesial and distal sites at baseline, 1, 7, 14, and 28 days. The GCF levels of OC and ICTP were detected by enzyme-linked immunosorbent assay (ELISA). The rate of tooth movement was evaluated at 2‑week intervals. Results: The amounts of canine distalization from baseline to 14 and 28 days in the piezocision group were significantly higher than the control group (P < 0.05). The GCF OC level of the piezocision group on the tension side and the ICTP level of the same group on the compression side were higher than the respective sides of the control group on day 14 (P < 0.05). Conclusions: Piezocision was found to be an effective treatment procedure for accelerating canine distalization accompanied by increased levels of OC and ICTP.Keywords: ICTP, osteocalcin, piezosurgey, tooth movement
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); ICTP; osteocalcin; piezosurgey; tooth movement